When knowledge is power: Evidence from the municipal bond market - Cuny, Christine (Journal of Accounting and Economics, 2018)
I investigate whether access to fundamental information enhances retail investors’ bargaining power, reducing the premium that small municipal bond investors pay over large investors. I find a reduction in this small trade premium after the introduction of an online disclosure repository that lowers retail investors’ information acquisition costs. This finding is limited to issuers whose disclosures are disseminated through the repository. The finding is pronounced for issuers that impose high information acquisition costs on investors ex-ante and those that exhibit high disclosure quality ex-post. These results suggest that as investors’ information sets align, so does their bargaining power with dealers.